Pengaruh Pemahaman Program Pendidikan Seksual Terhadap Perkembangan Moral Remaja Di SMP Negeri 1 Cipaku - Lia Yuliana; Deden Muhamad Ilham; Fayi Haikal Mahmud; Siti Zahrah Zaini; Shofi Qurrotua’ini; Nastiti Novitasari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the effect of sex education on the moral development of students at SMPN 1 Cipaku. The approach used was quantitative with a correlational design, involving 40 students as respondents. Validity and reliability tests showed that the instruments used were valid and reliable (Cronbach's Alpha = 0.838 for understanding sexual education and 0.811 for moral development). The results of Pearson correlation analysis showed a significant and strong relationship between understanding of sexual education and moral development of students (R = 0.720; p < 0.01). The results of simple linear regression showed that understanding of sex education has a significant positive effect on students' moral development with a regression coefficient of 0.546 (p = 0.000). However, barriers were found related to the limited implementation of sex education, which was conducted only once, causing inhomogeneity in students' understanding. This study suggests the need to increase the frequency and quality of sexual education programs that are more structured and sustainable, as well as the active involvement of parents to strengthen moral education at home. In addition, sexuality education should be integrated with moral values that are relevant to students' daily lives. In this way, a sustainable sexuality education program can have a greater impact on the moral formation of students in the future.